Random, double‐ and single‐strand DNA breaks can be differentiated in the method of Comet assay by the shape of the comet image. Issue 20 (1st September 2015) - Georgieva, Milena; Zagorchev, Plamen; Miloshev, George
<x xml:space="preserve">Abstract</x> Comet assay is an invaluable tool in DNA research. It is widely used to detect DNA damage as an indicator of exposure to genotoxic stress. A canonical set of parameters and specialized software programs exist for Comet assay data quantification and analysis. None of them so far has proven its potential to employ a computer‐based algorithm for assessment of the shape of the comet as an indicator of the exact mechanism by which the studied genotoxins cut in the molecule of DNA. Here, we present 14 unique measurements of the comet image based on the comet morphology. Their mathematical derivation and statistical analysis allowed precise description of the shape of the comet image which in turn discriminated the cause of genotoxic stress. This algorithm led to the development of the "CometShape" software which allowed easy discrimination among different genotoxins depending on the type of DNA damage they induce.